If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = 10x + 12 Reorder the terms: -11 + 3x = 10x + 12 Reorder the terms: -11 + 3x = 12 + 10x Solving -11 + 3x = 12 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -11 + 3x + -10x = 12 + 10x + -10x Combine like terms: 3x + -10x = -7x -11 + -7x = 12 + 10x + -10x Combine like terms: 10x + -10x = 0 -11 + -7x = 12 + 0 -11 + -7x = 12 Add '11' to each side of the equation. -11 + 11 + -7x = 12 + 11 Combine like terms: -11 + 11 = 0 0 + -7x = 12 + 11 -7x = 12 + 11 Combine like terms: 12 + 11 = 23 -7x = 23 Divide each side by '-7'. x = -3.285714286 Simplifying x = -3.285714286
| x-(x*0.25)-(x*0.3399)=50000 | | 0=16t^2-300t+2000 | | 21d^2-7d=O | | 6x+4y-2x+5y-5x= | | 12x^3-12x-45=0 | | x+.03x=23.6 | | t(n)=4n-2 | | 7(n-1)=-(3+n) | | k^2+5k-9=0 | | y=-1x^2+29x+12 | | 4r-10= | | 770=3x+77 | | x^2+x=-c | | 5.2+1.7n=1.12 | | 2m+k+3m+2k= | | k+1=k^2+k+c | | 3w+14=50 | | k=-2k^2-k | | 8x+7=5x-21 | | 3(p+4)=24 | | 4y+6y-5=10y-5 | | 5k+40L-35m= | | Sqrt(7x+44)=x | | Ix+7I=2 | | 9-7(5x-8)=63-9x | | 6(x+1)=2(3x+1)+4 | | 11x+5-3x+7= | | x^3+4*x^2+-11*x+30=0 | | 15(a)=225 | | 5x+3=7+5x | | 8(x-3)=-3x-17 | | -7(3x-5)+8=-21x+43 |